(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article examines the role, capabilities, and practical applications of Microsoft Excel and Power BI technologies in modern data analytics. As digital transformation continues to accelerate across industries, organizations increasingly face the challenge of collecting, processing, and analyzing large volumes of data to support effective decision-making. Consequently, the importance of advanced data management and visualization tools has grown significantly. The study explores the capabilities of Microsoft Excel in data processing, statistical analysis, financial modeling, and workflow automation. Furthermore, it analyzes the role of Power BI as a Business Intelligence (BI) platform, emphasizing its ability to create interactive dashboards, support real-time monitoring, and generate analytical insights through advanced data visualization and artificial intelligence features. The findings indicate that the integrated use of Excel and Power BI enhances organizational efficiency in data management, accelerates decision-making processes, and contributes to the optimization of business operations. The article highlights the growing significance of these technologies in the era of data-driven decision-making and digital transformation.